Standardization of the Krug clinical questionnaire - Elizalde Bravo, Roger (1998)
It is considered relevant to use for psychological evaluation not only tests madden especially for psychopathologic affected patients, but also for normal subjects. In this way, the Krug Clinic Questionnaire is a good option. Since it is practically unknown in our country, we try in this papa to give general approximations to this test, normalizing and adapting it for future use.